Pengaruh Media Pembelajaran Digital terhadap Minat dan Motivasi Belajar Anak Usia Dini - Angela Sariana Yuni (CV. Lentera Literasi Indonesia, 2026)
This study aims to analyze the effect of digital learning media on early childhood learning interest and motivation. The method used in this research is a Systematic Literature Review (SLR) by examining various scientific articles relevant to the research topic. The research process includes several stages, namely formulating research questions, searching and selecting articles, analyzing data, and interpreting the findings. The results show that digital learning media have a significant impact on improving children's learning interest and motivation. The use of media such as interactive videos, educational games, and learning applications can attract children's attention, increase focus, and stimulatecuriosity. In addition, digital media also help improve children's self-confidence and persistence in completing tasks through feedback and reward systems. However, the use of digital media also has negative impacts if not used wisely, such as the risk of gadget addiction, reduced social interaction, and health issues. Therefore, the role of teachers and parents is crucial in controlling and guiding the use of digital media to ensure it is balanced and appropriate to children's developmental stages. In conclusion, digital learning media can be an effective tool to enhance early childhood learning interest and motivation when used properly and appropriately.